Isolation of Lactic Acid Bacteria (LAB) from Digestive Tract of Asian Swamp Eel (Monopterus albus) and Bacterial Antagonist Test to Inhibit Pathogenic Bacteria Aeromonas hydrophila and Pseudomonas sp - Rudi Alfinda; Iesje Lukistyowati; Henni Syawal; Iskandar Putra (Jurnal Perikanan dan Kelautan, 2022)
Lactic Acid Bacteria (LAB) are probiotic-forming bacteria that have characteristics, like be able to ferment sugar or carbohydrates and produce lactic acid as the final product of fermentation. The purpose of this study was to obtain isolates of lactic acid bacteria from the digestive tract of Asian Swamp Eel (Monopterus albus) and to determine the inhibition produced by these lactic acid bacteria in inhibiting pathogenic bacteria such as Aeromonas hydrophila and Pseudomonas sp. The method was used in this study is experimental method, by taking the digestive tract of Asian Swamp Eel and then identifying the lactic acid bacteria and characterized by morphological and biochemical characteristics and tested of the antagonist against the pathogenic bacteria Aeromonas hydrophila and Pseudomonas sp. using the Kirby Bauer disc method (disc method). From the research results obtained 5 types of candidate lactic acid bacteria with each code BL121, BL263, BL142, BL242 and BL342. The five isolates of lactic acid bacteria were able to inhibit Aeromonas hydrophila and Pseudomonas sp. with a Inhibition range of 8-16 mm. Based on the results of the study, there were three isolates that had inhibitory power against bacteria A. hydrophila (12-16 mm) and Pseudomonas sp (11-13 mm) with codes BL121, BL263 and BL142 and were classified as strong. The identification results obtained are bacteria from the genus Bacillus sp